2018
DOI: 10.1007/s11606-018-4507-6
|View full text |Cite
|
Sign up to set email alerts
|

Maslach Burnout Inventory and a Self-Defined, Single-Item Burnout Measure Produce Different Clinician and Staff Burnout Estimates

Abstract: Point estimates of burnout notably differ between the self-defined and MBI measures. Compared to the MBI, the self-defined burnout measure misses half of high-burnout clinicians and more than 40% of high-burnout staff. The self-defined burnout measure has a low response burden, is free to administer, and yields similar associations across two burnout predictors from prior studies. However, the self-defined burnout and MBI measures are not interchangeable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 23 publications
4
65
1
5
Order By: Relevance
“…Clinic leaders, however, reported low rates of involuntary termination and retirement in both systems. There remains considerable variation in measuring burnout 28 ; this study used one of the most common approaches among studies of physicians and residents. 29 The 2013 and 2014 survey waves did not collect data on respondent sex or age, although tenure at the clinic is to some degree a proxy for age.…”
Section: Discussionmentioning
confidence: 99%
“…Clinic leaders, however, reported low rates of involuntary termination and retirement in both systems. There remains considerable variation in measuring burnout 28 ; this study used one of the most common approaches among studies of physicians and residents. 29 The 2013 and 2014 survey waves did not collect data on respondent sex or age, although tenure at the clinic is to some degree a proxy for age.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting certain aspects of the PA profession may serve to protect against burnout. First, PAs are trained to practice medicine as part of a health care team, and such team-based practice has been shown to cultivate an environment that reduces symptoms of burnout in primary care [61,62,63]. In addition to demonstrating the positive impact of a strong team culture, a study of primary care clinicians revealed that those working on a team in which they were regularly paired with the same medical assistant experienced less emotional exhaustion than non-team-based clinicians [62].…”
Section: Potential Protective Factorsmentioning
confidence: 99%
“…While PAs can change specialties, Hooker, Cawley, and Leinweber found that half of all PAs remained in their fi rst specialty throughout their careers [26]. This fi nding requires additional research, given that there may be an increased risk of burnout among clinicians in rural areas [10] and primary care settings [11,12,40,42,61]. The positive (engagement) and negative (burnout) infl uences on PA employment in specialties and practice settings may assist with PA recruitment and retention eff orts in areas with clinician shortages.…”
Section: Practice Setting and Its Eff Ect On Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the participants' current risk of burnout, five possible responses were dichotomised into two categories (symptoms of burnout versus no symptoms of burnout), as in other studies. 23,27 Questions were also dichotomised about current stress level, not enough time for a private life, and thoughts about leaving the profession after visual checks of the distributions using histograms. For the WEMWBS, means and 95% confidence intervals (CIs) were calculated using a crude regression model stratified by level of education.…”
Section: Data Managementmentioning
confidence: 99%